2011
DOI: 10.1093/ejcts/ezr114
|View full text |Cite
|
Sign up to set email alerts
|

Midterm follow-up dynamic echocardiography evaluation after ascending aorta replacement and reimplantation of the aortic valve (David operation) in a matched control study

Abstract: Although IAVA is significantly smaller after David procedure in comparison with matched controls, no pathological increase in TVG is noticed. A significant increase in the IAVA during physical stress documents the preserved pliability/elasticity of the aortic unit after David procedure preventing pathological increase in the TVG even during strenuous effort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Although this finding has no major clinical impact presently, this situation is not physiologic. In fact, we have recently documented that increased cardiac output achieved during maximal physical stress in adults is accompanied by a significant increase in the IAVA and a stable trans-AV gradient [10]. Interestingly, similar findings have been observed in patients that have undergone the David procedure in which the anatomically normal native AV is reimplanted in a straight Dacron tube.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although this finding has no major clinical impact presently, this situation is not physiologic. In fact, we have recently documented that increased cardiac output achieved during maximal physical stress in adults is accompanied by a significant increase in the IAVA and a stable trans-AV gradient [10]. Interestingly, similar findings have been observed in patients that have undergone the David procedure in which the anatomically normal native AV is reimplanted in a straight Dacron tube.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, similar findings have been observed in patients that have undergone the David procedure in which the anatomically normal native AV is reimplanted in a straight Dacron tube. In these patients, after exercise, the valve behaves much like the valve of normal subjects [10].…”
Section: Discussionmentioning
confidence: 92%
“…Several recent studies have shown that straight tube grafts also seem to respond to exercise by increasing the functional effective orifice during exercise. 24,25 Differences in acquisition methodology (echocardiogram vs magnetic resonance imaging) or possible oversizing of the straight tube (thus somehow creating more space and mimicking the presence of neosinuses) may explain these prior findings. Our current 4D flow results show a less favorable flow pattern, which is unlikely to result in substantial flow increase using the straight tube graft.…”
Section: Discussionmentioning
confidence: 99%
“…2 Resting mean systolic gradients were 4.3±2.1 mmHg and aortic valve orifice areas of 2.2±0.3 cm 2 , smaller mean values than reported by Mignosa et al 1 The first study prompted to examine the echocardiographic reports on 20 patients from our database and the aortic valve orifice areas index appeared to be a function of the size of the graft used for the reimplantation. 3 Since we have used the height of the cusps to select the size of the grafts, it seems that larger cusps will translate into large aortic valve orifice areas.…”
mentioning
confidence: 54%